Antioxidant Activity and Cytotoxicity against Cancer Cell Lines of the Extracts from Novel Xylaria Species Associated with Termite Nests and LC-MS Analysis - Niwana Wangsawat; Lutfun Nahar; Satyajit D. Sarker; Cherdchai Phosri; Andrew R. Evans; Anthony J. S. Whalley; Kiattawee Choowongkomon; Nuttika Suwannasai (MDPI AG, 2021)
Xylaria species associated with termite nests or soil have been considered rare species in nature and the few which have been reported upon have been found to act as a rich source of bioactive metabolites. This study evaluated 10 ethyl acetate extracts of five new Xylaria species associated with termite nests or soil for their antioxidant activity, and cytotoxicity against different cancer and normal cell lines. DPPH and ABTS radical scavenging activities of the extracts demonstrated strong capacity with low IC50 values. The highest observed activities belonged to X. vinacea SWUF18-2.3 having IC50 values of 0.194 ± 0.031 mg/mL for DPPH assay and 0.020 ± 0.004 mg/mL for ABTS assay. Total phenolic content ranged from 0.826 ± 0.123 to 3.629 ± 0.381 g GAE/g crude extract which correlated with antioxidant activities. The high total phenolic content could contribute to the high antioxidant activities. Cytotoxicity was recorded against A549, HepG2, HeLa and PNT2 and resulted in broad spectrum to specific activity depending on the cell lines. The highest activities were observed with X. subintraflava SWUF16-11.1 which resulted in 11.15 ± 0.32 to 13.17 ± 2.37% cell viability at a concentration of 100 µg/mL. Moreover, LC-MS fingerprints indicated over 61 peaks from all isolates. There were 18 identified and 43 unidentified compounds compared to mass databases. The identified compounds were from various groups of diterpenoids, diterpenes, cytochalasin, flavones, flavonoids, polyphenols, steroids and derivatives, triterpenoids and tropones. These results indicate that Xylaria spp. has abundant secondary metabolites that could be further explored for their therapeutic properties.